Financial impacts of the COVID-19 pandemic on immigrant communities in Portland Maine: a qualitative study - Eilish W. Carpenter; Claude Rwaganje; Michael Kohut; Elizabeth A. Jacobs; Kathleen M. Fairfield; Gloria D. Sclar (Archives of Public Health)
Abstract Background The COVID-19 pandemic not only disproportionately impacted the health of immigrants in the US, but led to financial disparities as well. However, few studies to date capture the experience of asylum-seeking and refugee populations. Methods We analyzed semi-structured interviews conducted in fall 2021 with immigrants (primarily asylum-seekers and refugees from countries in Central and East Africa) and key informants, and conducted focus group discussions in spring 2023 with employees of a non-profit supporting the financial needs of asylum-seekers and refugees in Portland, ME. Results We identified several ways in which the COVID-19 pandemic negatively impacted the financial stability of asylum-seekers and refugees, including: job loss, work permit backlog, lack of sick leave benefits, childcare expenses and related job strain, rising cost of basic goods, issues of housing availability/affordability, and healthcare expenses. Conclusion Policy changes that address structural factors and support financial stability among asylum-seekers and refugees and other low-income populations could help mitigate the impact of future public health crises and ultimately improve health equity.